2015
DOI: 10.1111/jpim.12292
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks for Innovation and New Product Development

Abstract: In this article we first provide a brief introduction into social network analysis, focusing on the measures and approaches that are used in the empirical contributions in this special issue. Second, we discuss the role of social networks in new product development. Social networks are inherently multilevel; we consider four “levels”: networks inside a firm, networks that cross firm boundaries, networks between firms, and networks that reside outside of the firm. Third, we discuss these four levels and highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 59 publications
2
64
1
6
Order By: Relevance
“…A study by De Jong and Den Hartog (2010) also confirmed that external work contacts are positively related to IWB. Leenders and Dolfsma (2016) highlighted that social networks inside a firm, between firms, and outside of the firm facilitate innovation, enabling employees to gather resources and learn about new ideas and perspectives, which may facilitate IWB. We also posit that task characteristics will have a stronger positive association with an individual's IWB when there is social support.…”
Section: Social Support Task Characteristics and Iwbmentioning
confidence: 99%
“…A study by De Jong and Den Hartog (2010) also confirmed that external work contacts are positively related to IWB. Leenders and Dolfsma (2016) highlighted that social networks inside a firm, between firms, and outside of the firm facilitate innovation, enabling employees to gather resources and learn about new ideas and perspectives, which may facilitate IWB. We also posit that task characteristics will have a stronger positive association with an individual's IWB when there is social support.…”
Section: Social Support Task Characteristics and Iwbmentioning
confidence: 99%
“…This will likely involve coupling secondary data with surveys or experiments. While innovation researchers have begun to examine the influence of innovators’ social networks (see the recent JPIM special issue: Leenders and Dolfsma, ), leveraging webscraped social media data will allow for evolving network patterns to be better understood.…”
Section: New Mechanisms Of Open Innovation and Opportunities For Datamentioning
confidence: 99%
“…The basic knowledge derived from in‐house development during the era of ferment allows firms to develop these social relations. Structurally embedded firms are able to use component suppliers and consultants as brokers to access spill‐over knowledge from competitors and firms from other industries with whom they are not directly connected (Granovetter, ; Leenders and Dolfsma, ). The structural embeddedness with suppliers also allows firms to benefit from their diverse experience (Weigelt and Sarkar, ), which is particularly useful in overcoming various learning‐by‐doing hurdles in integrating the external components (Attewell, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%